Financial Management and Commitment to Sending Remittances of Filipina Wives in Virginia, United States (Journal of Family Sciences, 2025)
Sending remittances back home may be a challenging financial task. Thus, this study was conducted to understand the financial management and commitment to sending remittances of nine Filipinas wives living in Virginia,  United States. Data was gathered through face-to-face in-depth interviews regarding their household finances, expenditures, experiences about balancing household budget, and sending remittances back home. Thematic analysis was used to analyze the qualitative data. Results show that some participants are dependent homemakers on their sole earner-husbands, indicating that each household has different sources and levels of income. All households practice financial management by having clear financial goals, a working monthly budget, being proactive budget holders and decision makers, and setting money aside for savings. Households have an allotted amount of monetary remittance that they send back home. The commitment to remitting is a personal choice of the Filipina wives to help their families of origin. However, emergency requests for additional remittances leave the monthly family budget  and savings at a potential risk for mismanagement. It should be made clear to the family of origin how much financial help can only be given so as not to  affect the financial management process of their female relative in the United States.